Hybrid unified power quality conditioner for power quality enhancement - Djellouli Djoudi; Benoudjafer Cherif; Toumi Toufik; Othmane Abdelkhalek (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
In a low-voltage electrical network, harmonics, reactive power, the current and voltage imbalance, and voltage dips have harmful effects on electrical equipments. To overcome these problems, the hybrid UPQC is proposed. This paper discusses the structure of passive filters, parallel active filters, serial and combines (UPQC) to study the compensation of all types of disturbances likely to appear in the grid. Furthermore, the aim of reducing the size, cost of UPQC is to improve the quality of electric power, making it in compliance with the new regulatory constraints, we proposed the hybrid UPQC which uses passive filters and a combination of active filters. To validate the proposed topology, several sags of source voltage have been applied, at the point of common coupling (PCC). The simulation results from MATLAB/Simulink are discussed to verify the proposed topology.